Genomic map of the functionally extinct northern white rhinoceros ( Ceratotherium simum cottoni ) - Gaojianyong Wang; Marisa L. Korody; Björn Brändl; Camilo Jose Hernandez-Toro; Christian Rohrandt; Karl Hong; Andy Wing Chun Pang; Joyce Lee; Giovanna Migliorelli; Mario Stanke; Sarah M. Ford; Iris Pollmann; et al. (Proceedings of the National Academy of Sciences, 2025)
The northern white rhinoceros (NWR; Ceratotherium simum cottoni ) is functionally extinct, with only two nonreproductive females alive. Efforts to rescue the NWR from its inevitable demise have inspired the exploration of unconventional conservation methods, including the development of induced pluripotent stem cells (iPSCs) for the in vitro generation of artificial gametes. The integrity of iPSC genomes is critical for in vitro gametogenesis to be used for assisted reproductive technologies using NWR iPSCs. We generated a chromosome-level NWR reference genome that meets or exceeds the metrics proposed by the Vertebrate Genome Project, using complementary sequencing and mapping methods. The genome represents 40 autosomes, an X and a partially resolved Y chromosome, and the mitochondrial genome. Using comparative FISH mapping, we confirmed a general gene order conservation between the NWR and horse genomes. We aligned the NWR genome with that of the southern white rhinoceros (SWR; Ceratotherium simum simum ), a population that has been physically separated from the NWR for tens of thousands of years, and we found that the two subspecies are very similar on the chromosome level. Comparing long-read data from NWR iPSC lines and the fibroblast cultures used for reprogramming, we identified copy number variations that were likely to have been introduced during in vitro iPSC expansion. The NWR reference genome allows for efficient, rapid, and accurate assessment of the genomic integrity of iPSC lines to direct their differentiation. This will assist in strategies to rescue the NWR through extraordinary measures like cloning and the generation of embryos from iPSC-derived gametes.